Comprehensive analysis of microRNA and metabolic profiles in bovine seminal plasma of different semen quality - Cao, Wei; Sun, Wenqiang; Chen, Shiyi; Jia, Xianbo; Wang, Jie; Lai, Songjia (Frontiers in Veterinary Science, 2023)
Background Seminal plasma plays a pivotal role in modulating sperm viability and function. However, the underlying mechanisms have not been fully elucidated. Method In this study, the bull semen production records of core breeding farms and bull stations in the past 10 years were analyzed. Results We found that the semen of 5-year-old bulls collected for the first time is of the best quality (p < 0.05). Despite the bull semen collected under the above conditions, low-quality sperm is still obtained from part of bulls due to individual differences. Interestingly, seminal plasma from normal semen is capable of improving low-quality semen motility. To identify the potential key factors in seminal plasma, the differences in miRNA and metabolite profiles between normal and low-quality seminal plasma were analyzed. We found that 59 miRNAs were differently expressed, including 38 up-regulated and 21 down-regulated miRNAs. Three hundred and ninety-one and 327 significantly different metabolites were identified from the positive and negative ion models, respectively. These multiple miRNAs and metabolites collectively contribute to the motility of sperm, subsequently, affect semen quality. Discussion Together, these results not only revealed the critical factors of seminal plasma improving sperm quality but also provided potential miRNA- or metabolite-based biomarkers to identify the high semen quality.